2015
DOI: 10.1016/j.nutres.2015.05.020
|View full text |Cite
|
Sign up to set email alerts
|

Probability and amounts of yogurt intake are differently affected by sociodemographic, economic, and lifestyle factors in adults and the elderly—results from a population-based study

Abstract: The aim of this population-based cross-sectional health survey (N = 532) was to investigate the factors associated with the probability and amounts of yogurt intake in Brazilian adults and the elderly. A structured questionnaire was used to obtain data on demographics, socioeconomic information, presence of morbidities and lifestyle and anthropometric characteristics. Food intake was evaluated using two nonconsecutive 24-hour dietary recalls and a Food Frequency Questionnaire. Approximately 60% of the subjects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 38 publications
0
5
0
1
Order By: Relevance
“…Moreover, in the available studies conducted among adults, the results are inconsistent. In Brazilian adults, a high socioeconomic status, including the high family income, was positively associated with the amount of yoghurt consumption [ 55 ], whereas, in young American adults, socioeconomic status had no effect on the amount of dairy consumption calculated in total or separately for milk, cheese and yogurt [ 56 ]. On the contrary, as Kapaj and Deci [ 57 ] indicated in their review book, socioeconomic characteristics influenced the consumption of dairy products all over the world.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in the available studies conducted among adults, the results are inconsistent. In Brazilian adults, a high socioeconomic status, including the high family income, was positively associated with the amount of yoghurt consumption [ 55 ], whereas, in young American adults, socioeconomic status had no effect on the amount of dairy consumption calculated in total or separately for milk, cheese and yogurt [ 56 ]. On the contrary, as Kapaj and Deci [ 57 ] indicated in their review book, socioeconomic characteristics influenced the consumption of dairy products all over the world.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of the socioeconomic factors for the acquisition of the food groups, especially for those food groups composed of milk and its derivatives, meats, fruits, greens, and vegetables, has already been documented in the literature [33,34]. Possa et al investigated the factors associated with yogurt consumption and observed a positive association between the amount of yogurt consumption and per capita family income: with increasing per capita family income, yogurt consumption increases by 0.61 g [22]. Considering the positive relationship between income and education, it is possible to explain the association observed in this study between the consumption of yogurt and higher levels of education.…”
Section: Discussionmentioning
confidence: 99%
“…The second stage was conducted within each censor sector using the proportional quotas relative to the following variables: sex (female, 64%; male, 36%), age (18-29 years, 29%; 30-39 years, 22%; 40-49 years, 25%; 50-59 years, 24%), and socioeconomic class (AB, 43%; C, 57%). The determination of the quotas was based on a study conducted by Possa et al, which aimed to verify the factors associated with yogurt consumption in Sao Paulo [22].…”
Section: Study Design and Populationmentioning
confidence: 99%
See 1 more Smart Citation
“…Importante ressaltar que o mesmo estudo permitiu caracterizar a população de consumidores de lácteos como fisicamente ativa, com reduzida probabilidade de fumar e menores concentrações de glicemia de jejum e TG, além de maiores concentrações de HDL-c. De forma similar, Chen et al (2014) ao analisarem mais de 190.000 indivíduos de 3 coortes americanos demonstraram que o consumo total de lácteos esteve inversamente correlacionado ao fumo, hipertensão e hipercolesterolemia e positivamente com atividade física e consumo de frutas e vegetais. Adicionalmente, apenas o consumo de iogurte permaneceu inversamente relacionado com o risco de DM2 após ajustes.Especificamente sobre iogurte,Wang et al (2013) estudaram sua associação com a qualidade da dieta e perfil metabólico em 6.526 adultos americanos e observaram que ao comparar indivíduos não consumidores à consumidores do produto, estes apresentaram melhores índices de qualidade da dieta, associado à maior prevalência no consumo de frutas, vegetais, peixes e grãos integrais, além de melhor perfil metabólico, caracterizado por menores valores de IMC e circunferência da cintura, níveis de pressão arterial, TG, glicemia e insulina de jejum e maiores níveis de HDL-c. Em adição, os autores verificaram uma menor prevalência de tabagismo nos consumidores de iogurtes, resultados semelhantes aos achados de estudo nacional transversal, onde ser consumidor de iogurte também foi associado a indivíduos não fumantes(POSSA et al, 2015).Outro importante estudo conduzido por Mozaffarian et al (2011) faz destaque ao iogurte em análise realizada em mais de 120.000 indivíduos participantes de 3 coortes americanos referente à mudanças no estilo de vida e sua relação com alterações no peso, onde o iogurte é apontado como o alimento que esteve associado ao menor ganho de peso a longo prazo. Do mesmo modo, os resultados de Martinez-Gonzalez et al (2014) demonstraram que as maiores frequências de consumo total de iogurte e isoladamente de sua versão integral estiveram associadas à menor incidência de sobrepeso/obesidade, sendo a força desta associação ainda maior dentre os participantes que relataram maior consumo de frutas.…”
unclassified